Using artificial intelligence technology in virtual court procedures - Ahmed Neama Attia (International Journal of Law Research and Studies, 2026)
In practice, litigation procedures face numerous difficulties, both logistically and within the judicial system. These procedures are often governed by established judicial custom, which relies on traditional approaches to administering the right to litigation. Requests for adjournment or expert assistance may be rejected by the presiding judge, who may believe these procedures delay and impede the resolution of the case. Caught between these beliefs and the judge’s authority to direct the course of proceedings, an alternative is needed to handle all types of cases—civil, criminal, administrative, and others. While this alternative is indeed human-made, it operates differently from its creators. This alternative is artificial intelligence (AI). The aim of this research is to enable AI to replace human intervention in civil litigation procedures, from filing the lawsuit and pleading to reviewing defenses and issuing a judgment, all without human intervention from the court. In other words, litigants file their cases with supporting documents, and AI handles the review, ensuring fairness for all parties involved, while emphasizing speed and accuracy. Resolving all cases, regardless of their number.